24t-8t^2= 0
8t(3-t)=0
8t=0 ======> t=0
3-t=0 =====> t=3
Solutions:
t=0
t=3
2007-05-19 04:06:01
·
answer #1
·
answered by gudspeling 7
·
3⤊
0⤋
24t-8t^2=0
8t(3-t)=0
this implies 8t=0 3-t=0
t=0 t=3
2007-05-20 10:23:29
·
answer #2
·
answered by srirad 2
·
1⤊
0⤋
24t - 8t² = 0
Divide thru the equation by 8
3t - t² = 0
Multiply thru by -1 to simplify
t² - 3t = 0
factor out a t
t(t - 3) = 0
Therefore
t = 0, t = 3
.
2007-05-19 11:22:29
·
answer #3
·
answered by Robert L 7
·
2⤊
0⤋
ok, the factorization methods are the easiest, but people have already explained those, but I thought I'd mention the quadratic equation because factorization doesnt always work.
in a quadratic formula you can always arange the terms to form something like:
ax^2 + bx + c = 0
with a, b and c being constants(positive OR negative)
so in this case:
a = -8
b = 24 and
c = 0
now the quadratic formula is as follows:
x = {-b +(or-) sqrt(b^2-4ac)}/2a
note that you'll get two solutions just as you should :) one with the +, one with the -. Google "quadratic formula" if you're having trouble with my notation. But yes, memorize this. Comes in very handy.
2007-05-19 11:41:06
·
answer #4
·
answered by lily_put 2
·
1⤊
0⤋
t could equal 0
2007-05-19 11:14:49
·
answer #5
·
answered by Brently L 1
·
0⤊
2⤋
why would i want to??
2007-05-19 11:04:25
·
answer #6
·
answered by hayles 3
·
0⤊
3⤋